Dielectric function modelling and sensitivity forecast for Au–Ag alloy nanostructures. Issue 26 (26th June 2020) - Wang, Xiu; Kan, Caixia; Xu, Juan; Zhu, Xingzhong; Jiang, Mingming; Ni, Yuan
Abstract : Based on theoretical calculations, FDTD simulations and experimental results, the refractive index sensitivity of Au–Ag alloy nanostructures were investigated, indicating the credibility and feasibility of the modelled dielectric data of alloy. Abstract : Plasmonic metal nanostructures are promising for chemical and biological sensor applications due to their high spectral sensitivity, defined as the relative shift in resonance wavelength with respect to the refractive index changes of the surroundings. In this work, the refractive index sensitivity (RI sensitivity) of one kind of core–shell nanostructure was studied, in which the gold nanobipyramid (AuBP) core was sheltered by the Au–Ag alloy shell. We investigated the dependence of the RI sensitivity and the figure of merit (FOM) of the localized surface plasmon resonance (LSPR) on the geometry and the composition of the nanostructures. Theoretical consideration on the LSPR revealed that the RI sensitivity of the nanostructures is determined by the bulk plasma wavelength, dielectric properties of the alloy and the geometrical parameters. To quantitatively explore the dependence of the RI sensitivity on the metal compositions and the aspect ratios of the nanostructures, the frequency-related dielectric properties of the alloy were calculated using the Drude-critical points model (DCPM). Then the calculated dielectric data were applied in the finite difference time domain (FDTD) solutions to simulate the optical spectra of the alloy nanostructures with various Ag concentrations. Experimentally, a series of fabrication processes were also carried out for the growth of a homogeneous Au–Ag alloy nanoshell on the surface of AuBPs using a wet-chemical method. The measured RI sensitivities agree well with the values predicted from FDTD simulations, indicating the availability, credibility and feasibility of the modelled dielectric data of the alloy. The DCPM and FDTD simulations can be combined to calculate the dielectric properties and forecast the sensitivity properties of the Au–Ag alloyed nanostructures with varying concentrations.